Challenges to international students in work-integrated learning: a scoping review. Issue 7 (10th November 2022) - Vu, Thai; Ferns, Sonia; Ananthram, Subramaniam
ABSTRACT: Work-integrated learning (WIL), particularly workplace-based WIL, provides international students with opportunities to be exposed to authentic working contexts, consequently enhancing student employability development. However, the literature indicates that many international students struggle in WIL despite continuous efforts by higher education institutions. A scoping review will inform future research and practice that seeks to enhance the WIL experiences of international students. This scoping review, guided by a transition framework, synthesized and analyzed findings from 22 empirical studies published during 2009–2020 related to challenges to international undergraduate students in WIL. Results show that while a range of challenges to this student cohort in WIL has been well established in the literature, little is known about how international students exercise their agency in navigating challenges to enhance WIL experiences. The scoping review has two major theoretical contributions: (i) establishing a novel typology of challenges to international students in WIL and (ii) proposing a context-specific research approach which facilitates inquiry into salient aspects of international students' WIL engagement in given contexts. The review concludes with recommendations for future research and practice from a transition perspective.